Efektivitas Model Challenge Based Learning Bernuansa Etnomatematika dengan Media Flipbook terhadap Peningkatan Kemampuan Berpikir Kritis Peserta Didik (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The development of critical thinking skills is an important goal of mathematics learning, but it has not yet developed optimally. One alternative learning model is Challenge Based Learning (CBL) with ethnomathematics nuances using flipbook media. This study aims to assess the effectiveness of this model on students' critical thinking skills. The study used a quantitative approach with a pretest-posttest control group design. The sample was selected using simple random sampling, obtaining class VIII A as the control and VIII B as the experiment. Data were obtained through tests and analyzed using one sample t-test, single sample proportion test, paired sample t-test, independent sample t-test with the assumption of unequal variance, and two sample proportion test. The results showed that Challenge Based Learning (CBL) with ethnomathematics nuances using flipbook media effectively improved students' critical thinking skills, as indicated by the average critical thinking ability of the experiment exceeding the BTA, classical learning completeness exceeding 75%, there was an increase in post-test scores compared to the pre-test, and the average, proportion of completeness, and improvement in critical thinking ability of the experiment were higher than the control. This study is limited to critical thinking skills, so further research is recommended to examine different learning abilities or models.